Alterations of Regional Homogeneity in Crohn's Disease With Psychological Disorders: A Resting-State fMRI Study - Huang, Mengting; Li, Xin; Fan, Wenliang; Li, Jing; Zhu, Liangru; Lei, Ping; Wu, Linxia; Sun, Qing; Zou, Yan; Han, Ping (Frontiers in Neurology, 2022)
Abnormal psychological processing in the central nervous system has been found in Crohn’s disease (CD) patients. Resting-state functional magnetic resonance images of 57 inactive and 58 active CD patients, and 92 healthy controls (HC) were obtained. The psychological assessment used a psychological questionnaire that was collected within 1 week before functional MRI examination. We investigated the neural basis of CD patients and the correlation among regional homogeneity (ReHo), clinical features and psychological assessment scores. We found that more severe psychological assessment disorder scores were observed in the active CD group than in the inactive CD group and HC group (P<0.001). Compared with HC, the active CD patients exhibited higher ReHo values in the frontal superior medial, frontal middle and lower values in the postcentral, supplementary motor area, and temporal middle. Meanwhile, inactive CD patients exhibited higher ReHo values in the frontal middle and lower ReHo values in the precentral, postcentral and putamen (all voxel P< 0.001, cluster P<0.01, corrected). The values of the frontal superior medial, postcentral and supplementary motor area were correlation with psychological assessment scores (r=0.38, -0.41, -0.32, P=0.001, 0.014, 0.003), and the clinical features of simple endoscopic score for Crohn’s disease and erythrocyte sedimentation rate were negatively correlated with psychological assessment scores in active CD patients (r=-0.35, -0.34, P=0.06, 0.08). These results provide evidence for abnormal resting-state brain activity in CD and suggest that the psychological of CD may play a critical role in brain function.